Mechanical Wave Concept Inventory: Developing The Diagnostic Test Four-Tier For Evaluation - Febrianto Putra; Budi Naini Mindyarto; Sulhadi Sulhadi (STKIP Singkawang, 2022)
Challenging for teachers in producing learning evaluation instruments that can diagnose students' abilities as well as student misconceptions was important. The diagnostic test four-tiers is one of the best assessment to diagnose students' misconceptions about physics concepts so that Mechanical Wave Concept Inventory has been developed in which form four-tiers diagnostic test. The instrument of the research are student sheet responses, and expert judgment reviews. Research and development frameworks' was included five processes that curriculum analysis processes, creating the design of the product, developing processes, implementing processes, and evaluating processes. The Pearson correlation sig. (2-tailed )resulted in which average r-count coefficient of 0.447 whose test instrument was concluded as valid. Alpha Cronbach's coefficient which was value of 0.90>0.70, so that the instrument was categorized as soon as possible reliable. Expert judgment index in which an average value of 0.87, that is categorized as very good. The quality of the questions was distributed with a classification of 24 good questions, 12 enough questions, and 4 bad questions. The difficulty level of the questions is divided into 7 questions in which easy categories as well as 33 questions in the medium category. Mechanical wave concept inventory was declared valid and reliable as well as good quality.